Analisis Perbandingan Performa Virtualisasi Server Sebagai Basis Layanan Infrastructure As A Service Pada Jaringan Cloud - Deni Marta; M. Angga Eka Putra; Guntoro Barovih (Universitas Bumigora, 2019)
Cloud Computing provides convenience and comfort to every service. Infrastructure as a Service is one of the cloud computing services that is a choice of several users, it is very important to know the performance of each existing platform in order to get the maximum result according to our needs. In this study, testing 3 platforms of cloud computing service providers are VMWare ESXi, XenServer, and Proxmox, using action research methods. From the results of performance measurements, then analyzed and compared with the minimum and maximum limits. The tested indicators are response time, throughput, and resource-utilization as a comparison of server virtualization performance implementations. In the resource utilization testing when the condition of installing an operating system, CPU usage on the Proxmox platform shows the lowest usage of 10.72%, and the lowest RAM usage of 53.32% also on the Proxmox platform. In the resource test utilization when idle state shows the lowest usage of 5.78% on the Proxmox platform, while the lowest RAM usage is 57.25% on the VMWare ESXi platform. The mean resource utilization tests indicate that the Proxmox platform is better. At the throughput test when the upload measurement of the XenServer platform is better 1.37 MB/s, while the throughput test when the download of the VMWare ESXi platform is better than 1.39 MB/s. On response time testing shows the platform VMWare ESXi as the fastest is 0.180 sec.